ModelTest-NG: A New and Scalable Tool for the Selection of DNA and Protein Evolutionary Models. (21st August 2019) - Darriba, Diego; Posada, David; Kozlov, Alexey M; Stamatakis, Alexandros; Morel, Benoit; Flouri, Tomas
Abstract: ModelTest-NG is a reimplementation from scratch of jModelTest and ProtTest, two popular tools for selecting the best-fit nucleotide and amino acid substitution models, respectively. ModelTest-NG is one to two orders of magnitude faster than jModelTest and ProtTest but equally accurate and introduces several new features, such as ascertainment bias correction, mixture, and free-rate models, or the automatic processing of single partitions. ModelTest-NG is available under a GNU GPL3 license at https://github.com/ddarriba/modeltest, last accessed September 2, 2019.